Розпаралелення алгоритму оптимізації параметрів дискретних динамічних моделей на масивно-паралельних процесорах - Козак, Ю.Я.; Стахів, П.Г.; Струбицька, І.П. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Method of paralleling task of parameters optimization of discrete dynamic models on massively parallel processors is proposed in this paper. Construct the block diagram of the algorithm, which allows a parallel implementation. Two methods for different areas of parallel algorithm are proposed.